Parenting Styles and Children’s Behaviors Difficulties (Indian Journal of Forensic Medicine & Toxicology, 2020)
The descriptive-correlation study design used to investigate the relation between parenting styles andchildren’s behavior difficulties by using the Parenting Styles and Dimensions Questionnaire, and Strengthsand Difficulties Questionnaire to achieve study objectives. An online questionnaire applied as a method ofdata collecting on 101 parents (majority of them mothers) and their 4-11 years old children, 58 of them weremales and 43 were females. The finding of the current study reveals that the authoritative parenting style wasused more than other styles and correlated significantly with good child behaviors while the authoritarianand permissive style used less and correlated negatively with child’s behaviors. In conclusion, when parentsuse an authoritative or democratic style enhances children’s positive behaviors more than other styles.
Keywords: Parenting styles, behavior’s problems, and behavior’s difficulties